Thermal Insulation and Mechanical Properties in the Presence of Glas Bubble in Fly Ash Geopolymer Paste - Noor Fifinatasha Shahedan; Mohd Mustafa Al Bakri Abdullah; Norsuria Mahmed; Liew Yun Ming; Shayfull Zamree Abd Rahim; Ikmal Hakem A Aziz; Aeslina Abdul Kadir; Andrei Victor Sandu; Mohd Fathullah Ghazali (Archives of Metallurgy and Materials, 2022)
The density, compressive strength, and thermal insulation properties of fly ash geopolymer paste are reported. Novel insulation material of glass bubble was used as a replacement of fly ash binder to significantly enhance the mechanical and thermal properties compared to the geopolymer paste. The results showed that the density and compressive strength of 50% glass bubble was 1.45 g/cm3 and 42.5 MPa, respectively, meeting the standard requirement for structural concrete. Meanwhile, the compatibility of 50% glass bubbles tested showed that the thermal conductivity (0.898 W/mK), specific heat (2.141 MJ/m3K), and thermal diffusivity (0.572 mm2/s) in meeting the same requirement. The improvement of thermal insulation properties revealed the potential use of glass bubbles as an insulation material in construction material.